1996
DOI: 10.1046/j.1365-2249.1996.d01-729.x
|View full text |Cite
|
Sign up to set email alerts
|

Soluble adhesion molecules in sera of patients with leprosy: levels of soluble intercellular adhesion molecule-1 (sICAM-1) rapidly decrease during multi-drug therapy

Abstract: SUMMARYThe clinicopathological spectrum of leprosy is associated with an altered immunological reaction. The expression of adhesion molecules on endothelial cells directs the cellular traffic to sites of local skin and nerve inflammation. Soluble forms of adhesion molecules, which are released upon cytokine activation, can be detected in the circulation and may reflect ongoing tissue inflammation. We determined the serum levels of sICAM-1, sE-selectin and sL-selectin in 74 patients with leprosy (tuberculoid fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The intensity of the localized inflammation is reflected by raised serum levels for TNF, 25 soluble IL-2 receptors 26 and adhesion molecules. 27 The institution of effective anti-inflammatory therapy rapidly reverses these abnormalities.…”
Section: Prevalence Of Reversal Reactionsmentioning
confidence: 99%
“…The intensity of the localized inflammation is reflected by raised serum levels for TNF, 25 soluble IL-2 receptors 26 and adhesion molecules. 27 The institution of effective anti-inflammatory therapy rapidly reverses these abnormalities.…”
Section: Prevalence Of Reversal Reactionsmentioning
confidence: 99%
“…In leprosy, the elevation of adhesion molecules was demonstrated in different cell types along the spectrum of the disease. Among adhesion molecules evidenced in leprosy, it is possible to highlight the intercellular adhesion molecule-1 (ICAM-1) and its ligand, lymphocyte function-associated antigen-1 (LFA-1) ( Sullivan et al 1991 , Rieckmann et al 1996 ), E-selectin ( Rieckmann et al 1996 ), as well as vascular cell adhesion molecule 1 (VCAM-1) ( Martinuzzo et al 2002 ).…”
mentioning
confidence: 99%
“…Direct contact with activated peripheral blood T cells, human T cell lines, or membrane preparations of activated T lymphocytes has been demonstrated to stimulate monocytes and monocytic cell lines, in vitro, to produce proinflammatory cytokines, including TNF-a, IL-6, and IL-1b [16][17][18]. Although previous studies have identified significant modulation in integrin expression during ENL reactions [19,20], the synergistic or independent role of cell-cell contact in the generation of TNF-a in leprosy has not been characterized.…”
mentioning
confidence: 99%